2015
DOI: 10.1111/fwb.12621
|View full text |Cite
|
Sign up to set email alerts
|

Functional trait responses of aquatic macroinvertebrates to simulated drought in a Neotropical bromeliad ecosystem

Abstract: Summary The duration of the dry seasons in south‐eastern Amazonia is expected to increase. Little is known of how freshwater assemblages respond to drought in the humid rainforests and of the extent to which they resist the absence of rainfall before the collapse of the system. We manipulated rainshelters over tank‐forming bromeliads (i.e. the interlocking leaf axils of these plants form wells that collect rainwater) to simulate an exceptionally long dry period (49 days, compared with a 10‐year mean ± SD ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 51 publications
8
54
1
3
Order By: Relevance
“…Esta resistencia se atribuye a la presencia de estructuras tales como branquias (Dero, Ancylidae Mf., Pyrgophorus), conchas para proteger el cuerpo o pigmentos como la hemoglobina (Chironomus), así como de mecanismos especializados que les permiten salvaguardarse de dichas condiciones. Estas formas de especialización de los macroinvertebrados ante las condiciones físicas y químicas adversas encontradas en la isla de Providencia concuerdan con lo hallado para ríos intermitentes de Australia, España y Estados unidos (Beche et al 2006, Bonada et al 2007, Dézerald et al 2015, Huryn et al 2008, Stubbington et al 2016). …”
Section: Macroinvertebrados a Pesar Del Aislamiento De La Isla De Prunclassified
See 2 more Smart Citations
“…Esta resistencia se atribuye a la presencia de estructuras tales como branquias (Dero, Ancylidae Mf., Pyrgophorus), conchas para proteger el cuerpo o pigmentos como la hemoglobina (Chironomus), así como de mecanismos especializados que les permiten salvaguardarse de dichas condiciones. Estas formas de especialización de los macroinvertebrados ante las condiciones físicas y químicas adversas encontradas en la isla de Providencia concuerdan con lo hallado para ríos intermitentes de Australia, España y Estados unidos (Beche et al 2006, Bonada et al 2007, Dézerald et al 2015, Huryn et al 2008, Stubbington et al 2016). …”
Section: Macroinvertebrados a Pesar Del Aislamiento De La Isla De Prunclassified
“…Los rasgos que predominan varían dependiendo de si la sequía es estacional predecible o si es un evento impredecible (Bogan et al 2015, Lake 2003. En general, se ha encontrado en ecosistemas mediterráneos y templados que los rasgos funcionales asociados con mayor adaptación a la temporalidad son: ciclos vitales flexibles (sincronización de los ciclos de vida acuáticos con las temporadas de lluvias), desarrollo ligado con la temperatura del agua, diapausa, huevos protegidos contra la desecación y alto poder de dispersión (Bonada et al 2007, Boulton 1989, Dézerald et al 2015, Dole-Olivier et al 1997, Lake 2003, McDonough et al 2011, Stubbington et al 2016, Williams y Hynes 1977, así como alimentación de tipo generalista (Dieterich y Anderson 2000).…”
unclassified
See 1 more Smart Citation
“…Beyond values of light intensity and temperature of stored water, canopy cover influenced only the amount of CPOM in bromeliads. However, the volume of water and the amount of FPOM, which are important variables for the colonization process (Kitching, 2000;Armbruster et al, 2002;Dézerald et al, 2015b), did not differ between treatments and contributed to the high similarity of the communities sampled throughout the experiment. These results differ from those found in studies developed in tropical forest ecosystems (Montero et al, 2010;González et al, 2014) and are probably related to the characteristics of restinga (i.e., less dense vegetation composed of species adapted to low water availability and high temperatures and solar radiation) (Zaluar and Scarano, 2000;Scarano, 2002).…”
Section: Shadedmentioning
confidence: 99%
“…Some studies have suggested the volume of water is the main factor that influences the colonization of phytotelm ecosystems because it determines habitat size and susceptibility to colonization (Srivastava et al, 2008;Dézerald et al, 2014;Gossner et al, 2016). Although unshaded bromeliads have higher capacity of water collection (Déz-erald et al, 2014), tanks held by these plants are also subject to higher evaporation rates as a result of direct exposure to solar radiation (Dézerald et al, 2015b;Buosi et al, 2015). In this study, the volumes of stored water differed only between colonization times and were related to rainfall values during the experiment.…”
Section: Shadedmentioning
confidence: 99%